Pelatihan Business Model Canvas untuk Meningkatkan Kompetensi Wirausaha Siswa SMA - Putra, Ida Bagus Ardhi; Darmawan, I Made Dwi Hita; Dewi, Desak Putu Nitya (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2024)
The government has implemented entrepreneurship education at many levels of school with the main goal of producing experienced and talented young entrepreneurs to maintain the workforce and reduce unemployment. The core of entrepreneurship education is to prepare students to have the ability, thinking, and managerial capacity, as well as entrepreneurial skills, not just working for a salary. One important concept in entrepreneurship education is the Business Model Canvas (BMC). This model is used to describe, visualize, assess, and update business models, in order to obtain optimal performance. Santo Yoseph Catholic High School (SMAK) Denpasar is a private high school located at Denpasar, Bali. The community service carried out was in the form of BMC training activities. The aim is to increase and develop students' entrepreneurial insights, especially related to BMC for SMAK Santo Yoseph Denpasar students. This activity was attended by 46 students. The activity began with the presentation of BMC material by the resource person. The event continued with the practice of making BMC by student groups according to their business ideas. This activity has provided benefits to students so that they are able to make BMC well which they can use to describe, design, and change business models effectively.